Estimation of Growth Rate and Decomposition of Output Components of Oilseed: A Comparative Study among the States of North East - Singh, N. Uttam; Das, Kishore K; Roy, A.; Tripathy, A. K. (Indian Journal of Hill Farming, 2016)
This paper investigates the trends in area, production and yield of oilseed in the states of north east India by using component analysis model. The study period was from 1982-83 to 2011-12 and it had been divided into three periods: 1982-83 to 1991-92, 1992-93 to 2001-02, 2002-03 to 2011-12 to have an understanding of decadal performance. The results clearly showed that the growth rate performance of area, production and yield of oilseed in the region declined sharply from period 1 to 3. The study witnessed that more than half of the area under the crop in the region suffered from low growth rate in production. The comparison of production growth rates in all the periods revealed that Nagaland show better performance followed by Arunachal Pradesh, Meghalaya, Mizoram and Sikkim while Assam, Manipur and Tripura are running behind. Performance of Nagaland was even better than the north east total and national level. Area growth was also best achieved by Nagaland followed by Arunachal Pradesh, Meghalaya and Sikkim. The decomposition analysis of growth suggests that sources of output growth in north east were the same in all the three periods as the major contribution was yield effect followed by area effect. In all the eight states for all the period the relative contribution to the change of output was either yield effect or area effect except in few cases.